ANALISIS KEBIJAKAN ISENTIF PAJAK DI TENGAH WABAH COVID-19 DI INDONESIA - Alda Sitohang; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This study aims to analyze tax incentive policies in Indonesia due to the corona virus outbreak. This research uses literature study as a method. The data processing and analysis technique used is content analysis. The main data from this research is the Regulation of the Minister of Finance of the Republic of Indonesia. As well as other data obtained through text books, journals, theses, articles, information from the internet and other official websites. The results show that the tax incentive policy set by the government is conceptually and its implementation is quite good, the regulations referenced in this study have a longer tax period than the previous tax period regulations. However, tax incentives have not been well realized due to a decrease in state revenue which causes the total state revenue to fall short of the stipulated budget amount.